Produk Inovatif Sabun Mandi Berbahan Dasar Minyak Kayu Putih Kampung Wasur Merauke - Pandiangan, Nurlela; Siregar, Lamtiar Ferawaty; Meilvidiri, Wayrohi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Eucalyptus oil leaves are one of the natural potentials of Wasur Village which is very useful and has selling value. So far, eucalyptus oil leaves are managed by the Wasur Village community to be made into eucalyptus oil and sold. The Wasur Village community only processes Eucalyptus Oil Leaves into Essential Oil, while Eucalyptus Oil Leaves can be processed into various useful products such as Bath Soap. This community pasrtnership service (PKM) activity was carried out in Wasur Village, Merauke, South Papua. This Activity aims to provide training to the Wasur Village community on how to process Eucalyptus Oil Leaves into Bath Soap as an innovative product that can be traded. This activity resulted in as increase in the production of the Wasur Village community through the addition of new innovative Bath Soap products that can be traded to increase community income.